Safety and efficacy of novel oblique-viewing scope for B2-endoscopic ultrasound-guided hepaticogastrostomy - Sho Ishikawa; Kazuo Hara; Nozomi Okuno; Nobumasa Mizuno; Shin Haba; Takamichi Kuwahara; Yasuhiro Kuraishi; Takafumi Yanaidani; Masanori Yamada; Tsukasa Yasuda; Toshitaka Fukui; Teru Kumagi; et al. (Clinical Endoscopy, 2024)
Background/Aims Endoscopic ultrasound (EUS)-guided hepaticogastrostomy (EUS-HGS) performed at the intrahepatic bile duct segment 3 (B3) is widely used for biliary drainage. Although performing post-puncture procedures is easier in the intrahepatic bile duct segment 2 (B2) when using a conventional oblique-viewing (OV) EUS scope, this method may cause transesophageal puncture and severe adverse events. We evaluated the safety and efficacy of B2 puncture using a novel OV-EUS scope. Methods In this single-center retrospective study, we prospectively enrolled and collected data from 45 patients who consecutively underwent EUS-HGS procedures with a novel OV-EUS scope between September 2021 and December 2022 at our cancer center. Results The technical success rates of B2-EUS-HGS and EUS-HGS were 93.3% (42/45) and 97.8% (44/45), respectively. The early adverse event rate was 8.9% (4/45) with no cases of scope changes or transesophageal punctures. The median procedure time was 13 minutes (range, 5–30). Conclusions B2-EUS-HGS can be performed safely with the novel EG-740UT (Fujifilm) OV-scope without transesophageal puncture and with a high success rate. B2-EUS-HGS using this novel OV scope may be the preferred strategy for EUS-HGS.